Research progress on nutritional support in the neonatal and pediatric populations receiving extracorporeal membrane oxygenation - Zhang, Hongquan; Zhao, Lizhuo; Jia, Baohui (Frontiers in Nutrition, 2024)
Nutritional support is crucial for the prognosis of children supported by extracorporeal membrane oxygenation (ECMO). This article discusses the latest research progress and guideline recommendations for nutritional support during ECMO. We summarize the nutritional status and evaluation of ECMO patients, nutritional support methods and timing, trace elements, the impact of continuous renal replacement therapy (CRRT), and energy requirements and algorithms. The article shows that malnutrition is high in ECMO patients compared to other critically ill patients, with nearly one-third of patients experiencing a decrease in nutritional indicators. The timing of the initiation of nutrition is very important for the nutritional status of the child. Early enteral nutrition can improve patient prognosis, which is the most commonly used, with parenteral nutrition as a supplement. However, the proportion of enteral nutrition is relatively low, and a stepwise nutrition algorithm can determine when to initiate early enteral nutrition and parenteral nutrition. Malnourishment during critical illness have been associated with increased morbidity as well as increased mortality. Nutritional status should be evaluated at admission by screening tools. In addition, changes in the levels of several metabolites in vivo, such as blood lipids, carnitine, and thiamine, can also reflect the degree of nutritional deficiency in critically ill children. This article provides a reference for the implementation of nutrition of pediatric ECMO patients and further research on nutritional support.